Kaji Pengaruh Bahan Isolasi Terhadap Perpindahan Panas pada Kotak Penyimpan Nugget - - Alchalil; Ahmad Syuhada; - Hamdani (Jurnal Teknik Mesin Unsyiah, 2013)
Nugget is one of food ready to served which raw material was a chicken meat. The aimed this research is to get a limited or how long time to save nugget that defended the temperature 0oC, with need time 2 – 4 days only,which made from a wood and styrofoam. From the result of research that the wood box able to defended the temperature in 0oC at the fiftieht hours,styrofoam box at sixty fourth hours and mixture box in seventy one hours. The temperature on nugget (T1) wood box from the first hour until thirty ninth hours experienced rise of temperature lower than mixture box and styrofoam. The temperature on the box (T2)   wood box from the first hours  until fourty sixth huors experienced rise of the temperature lower than mixture box and styrofoam box.